Graphene-reinforced photocured 3D printed silicon-based ceramic and preparation method and application thereof
Patent Information
- Application Number
- CN202411293655.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-09-14
AI Technical Summary
但是由于氧化硅与光固化所用的光敏树脂折射率接近,容易导致极大的过度固化区域,使得制备出的陶瓷素坯精度严重下降,不利于陶瓷型芯的实际应用
[0025]1、本发明将石墨烯引入光固化3D打印,基于其卓越的吸光特性,有效改善了紫外光与陶瓷颗粒的复杂耦合作用,显著抑制了过度固化区域,从而调控其成形精度,使其坯体尺寸与设计尺寸相吻合。在烧结阶段,石墨烯可作为收缩补偿剂,通过其氧化膨胀生成CO2,从而抑制烧结收缩,并提高气孔率,有助于后续的脱除工艺以及涡轮叶片的精度。由此可同时优化硅基陶瓷型芯在固化成形-烧结收缩阶段的尺寸精度。通过引入硼化硅和硼化锆使其在高温烧结过程中被氧化,分别生成氧化硅与氧化锆,一方面,生成的氧化硅可以很好的补充硅源并相变生成方石英增强基体强度。另一方面,氧化锆在1200℃下由单斜相转变为四方相,促进微裂纹的形成,增加了能量损耗机制,缓解了应力集中现象,更好的提升了陶瓷型芯的断裂韧性与弯曲强度。
Smart Images

Figure CN119143489B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic additive manufacturing technology, specifically relating to a graphene-enhanced photopolymerization 3D printing silicon-based ceramic, its preparation method, and its application. Background Technology
[0002] Ceramic cores, as key transitional components in forming the complex air-cooled structures of turbine blades for aero-engines, can effectively improve aero-engine performance. Traditional ceramic core fabrication processes, such as hot-press casting and gel casting, heavily rely on molds and suffer from drawbacks such as long development cycles and high costs, making it difficult to form ceramic cores with complex structures. In contrast, ceramic 3D printing technology, with its mold-free process and excellent surface quality, can be applied to the integrated forming of complex ceramic core structures.
[0003] Silica-based ceramics are widely used in ceramic cores due to their excellent high-temperature stability and ease of removal. However, because the refractive index of silica is close to that of the photosensitive resin used in photocuring, it easily leads to a large over-curing region, resulting in a significant decrease in the precision of the prepared ceramic preform, which is detrimental to the practical application of ceramic cores. During the subsequent debinding and sintering process, the ceramic undergoes sintering shrinkage due to densification, further reducing dimensional accuracy. Patent CN117303870A discloses a photocurable additive manufacturing method for zero-sintering-shrinkage aluminum-based ceramic cores, which significantly reduces sintering shrinkage but does not address the impact of the curing stage on the precision of the ceramic core. Therefore, controlling the dimensional accuracy of ceramic cores during both the curing and sintering shrinkage stages is a major challenge for silicon-based ceramic cores. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to address the shortcomings of the prior art by providing a graphene-enhanced photopolymerization 3D printing silicon-based ceramic, its preparation method and application. This method can simultaneously adjust the dimensional accuracy of photopolymerization 3D printing silicon oxide ceramic curing-forming-sintering shrinkage to obtain silicon-based ceramic cores with excellent comprehensive performance, thereby promoting the application of ceramic 3D printing technology in the field of precision casting.
[0005] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a graphene-enhanced photopolymerization 3D printing silicon-based ceramic, wherein the graphene-enhanced photopolymerization 3D printing silicon-based ceramic is made from the following raw materials in volume fractions: 32% to 44% photosensitive resin, and the remainder is silicon-based composite ceramic powder;
[0006] The silicon-based composite ceramic powder is composed of the following raw materials in parts by weight: 70-90 parts matrix material, 10-25 parts mineralization modifier, and 0 parts < graphene < 0.1 parts; graphene is used as a precision control agent.
[0007] The photosensitive resin is composed of the following raw materials in the indicated mass fractions: 1% to 5% photoinitiator, 5% to 10% dispersant, and the remainder being crosslinking aids;
[0008] The matrix material is fused silica;
[0009] The mineralization modifier is a mixture of silicon boride and zirconium boride;
[0010] The crosslinking aid is a mixture of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, isoborneol acrylate, and isoborneol methacrylate;
[0011] The dispersant is BYK9076, BYK111, or KOS110;
[0012] The photoinitiator is 1-hydroxycyclohexylphenyl ketone or trimethylbenzoyl-diphenylphosphine oxide.
[0013] Preferably, the fused silica includes fused silica with three particle size ranges: 0μm < d1 ≤ 5μm, 5μm < d2 ≤ 15μm, and 15μm < d2 ≤ 30μm.
[0014] Preferably, the crosslinking aid is composed of the following raw materials in parts by weight: 50 to 70 parts of 1,6-hexanediol diacrylate, 20 to 50 parts of trimethylolpropane triacrylate, 10 to 20 parts of isoborneol acrylate, and 10 to 20 parts of isoborneol methacrylate.
[0015] Isoborneol acrylate, isoborneol methacrylate, and 1,6-hexanediol diacrylate have a low number of functional groups, which can effectively reduce the viscosity of ceramic slurry; trimethylolpropane triacrylate is a trifunctional organic compound, which can effectively promote photopolymerization reaction and improve printing efficiency.
[0016] Preferably, the mineralization modifier is a powder with a particle size of 20μm to 50μm.
[0017] This invention also provides a method for preparing the above-mentioned graphene-reinforced photopolymerization 3D printed silicon-based ceramics, the method being as follows:
[0018] S1. The photosensitive resin and silicon-based composite ceramic powder are ball-milled at a speed of 300 rpm to 600 rpm for 3 h to 5 h to obtain a ceramic slurry that can be used for photocuring.
[0019] S2. Place the photopolymerizable ceramic slurry obtained in S1 into a ceramic 3D printer. Set the printing layer thickness to 50μm~150μm, the ultraviolet wavelength to 405nm, the exposure time to 3s~5s, and the exposure power to 10mW / cm / cm²~30mW / cm². 2After layer-by-layer printing, a ceramic core blank is obtained;
[0020] S3. The ceramic core blank obtained in S2 is placed in a muffle furnace for degreasing treatment. Under air atmosphere, the temperature is increased from room temperature at a heating rate of 0.1℃ / min to 0.5℃ / min. After holding at 200℃, 431℃, 508℃ and 600℃ for 1h to 2h respectively, the degreased silicon-based ceramic is obtained.
[0021] S4. Place the degreased silicon-based ceramic obtained in S3 into a sintering furnace. Under an air atmosphere, heat the ceramic from room temperature to 1150℃ to 1250℃ at a heating rate of 0.1℃ / min to 0.5℃ / min, hold it at that temperature for 4h to 8h, and then cool it to 900℃ at a cooling rate of 1℃ / min to 4℃ / min. Finally, cool the ceramic to room temperature with the furnace to obtain graphene-reinforced photopolymerized 3D printed silicon-based ceramic.
[0022] Preferably, the over-curing width of the graphene-enhanced photopolymerized 3D printed silicon-based ceramic in S4 is -50.34μm to 52.09μm, the sintering shrinkage rate is 2.70% to 3.16%, and the porosity is 26.69% to 27.7%.
[0023] The present invention also provides the application of the above-mentioned graphene-enhanced photopolymerization 3D printing silicon-based ceramics, wherein the graphene-enhanced photopolymerization 3D printing silicon-based ceramics are used for precision casting of ceramic cores.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] 1. This invention introduces graphene into photopolymerization 3D printing. Based on its superior light absorption properties, it effectively improves the complex coupling effect between ultraviolet light and ceramic particles, significantly suppressing over-curing regions and thus controlling the forming accuracy to ensure the blank size matches the design size. During the sintering stage, graphene acts as a shrinkage compensator, generating CO2 through its oxidative expansion, thereby inhibiting sintering shrinkage and increasing porosity, which is beneficial for subsequent removal processes and the accuracy of turbine blades. This simultaneously optimizes the dimensional accuracy of silicon-based ceramic cores during the curing-sintering shrinkage stage. By introducing silicon boride and zirconium boride, which are oxidized during high-temperature sintering, silicon oxide and zirconium oxide are generated respectively. On one hand, the generated silicon oxide can effectively supplement the silicon source and undergo phase transformation to generate cristobalite to enhance the matrix strength. On the other hand, zirconium oxide transforms from a monoclinic phase to a tetragonal phase at 1200℃, promoting microcrack formation, increasing energy loss mechanisms, alleviating stress concentration, and further improving the fracture toughness and flexural strength of the ceramic core.
[0026] 2. The graphene-enhanced photopolymerization 3D printing silicon-based ceramic prepared by this invention has an over-curing thickness of 0 μm, a sintering shrinkage rate of 2.70% to 3.16%, and a porosity of 26.69% to 27.7%. It synergistically controls the dimensional changes during forming and sintering, and realizes high-precision additive manufacturing of silicon-based ceramic cores.
[0027] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments. Attached Figure Description
[0028] Figure 1 These are the photocuring accuracy test diagrams from Examples 1-5 of this invention.
[0029] Figure 2 The image shows the microstructure of the photocurable silicon-based ceramic core prepared in Example 1 of this invention.
[0030] Figure 3 This is a physical image of the complex structure sample prepared according to the present invention.
[0031] Figure 4 The diagram shows the physical properties of the ceramic cores in Examples 1-5 of this invention. Detailed Implementation
[0032] Example 1
[0033] The graphene-enhanced photopolymerizable 3D printed silicon-based ceramic of this embodiment is made from the following raw materials by volume fraction: 35% photosensitive resin, and the remainder is silicon-based composite ceramic powder.
[0034] The silicon-based composite ceramic powder is composed of the following raw materials in parts by weight: 90 parts matrix material, 10 parts mineralization modifier, and 0.0006 parts graphene.
[0035] The photosensitive resin is composed of the following raw materials in the indicated mass fractions: 4% photoinitiator, 8% dispersant, and the remainder being crosslinking aids;
[0036] The matrix material is fused silica; the fused silica includes fused silica with three particle size ranges in a mass ratio of 7:2:1: 0μm<d1≤5μm, 5μm<d2≤15μm, and 15μm<d2≤30μm.
[0037] The mineralization modifier is a powder mixture of silicon boride and zirconium boride with a particle size of 20 μm and a mass ratio of 1:1.
[0038] The crosslinking aid is composed of the following raw materials in parts by weight: 60 parts of 1,6-hexanediol diacrylate, 20 parts of trimethylolpropane triacrylate, 10 parts of isoborneol acrylate, and 10 parts of isoborneol methacrylate.
[0039] The dispersant is BYK111 (BYK Chemical Dispersant-111);
[0040] The photoinitiator is trimethylbenzoyl-diphenylphosphine oxide.
[0041] This embodiment also provides a method for preparing the above-mentioned graphene-enhanced photopolymerization 3D printed silicon-based ceramics, the method being as follows:
[0042] S1. Photosensitive resin and silicon-based composite ceramic powder are ball-milled at a speed of 600 rpm for 4 hours using zirconia ball milling beads as the medium to obtain a ceramic slurry that can be used for photocuring.
[0043] S2. Place the photopolymerizable ceramic slurry obtained in S1 into a ceramic 3D printer. Set the printing layer thickness to 100μm, the ultraviolet wavelength to 405nm, the exposure time to 5s, and the exposure power to 15mW / cm². 2 After layer-by-layer printing, a ceramic core blank is obtained;
[0044] S3. The ceramic core blank obtained in S2 is placed in a muffle furnace for degreasing treatment. Under air atmosphere, the temperature is increased from room temperature at a heating rate of 0.2℃ / min. After holding at 200℃, 431℃, 508℃ and 600℃ for 2 hours respectively, the degreased silicon-based ceramic is obtained.
[0045] S4. Place the degreased silicon-based ceramic obtained in S3 into a sintering furnace, and heat it from room temperature to 1200℃ at a heating rate of 0.2℃ / min under air atmosphere, hold it at that temperature for 6 hours, and then cool it down to 900℃ at a cooling rate of 2℃ / min. After cooling it to room temperature with the furnace, graphene-reinforced photocurable 3D printed silicon-based ceramic is obtained.
[0046] The exposure performance of the graphene-reinforced photopolymer 3D printed silicon-based ceramic prepared in this embodiment was tested. The results showed that the over-curing width was 52.09 μm. The physical properties of the obtained ceramic core were tested, and the results showed that the shrinkage rate was 3.16% and the porosity was 24.33%.
[0047] This embodiment also provides the application of the above-mentioned graphene-enhanced photopolymerization 3D printed silicon-based ceramics, which are used for precision casting of ceramic cores.
[0048] This embodiment can effectively adjust the forming accuracy of silicon-based ceramic cores manufactured by photopolymer additive manufacturing and suppress sintering shrinkage, avoid the generation of interlayer cracks during debinding and sintering, and obtain silicon-based ceramic cores with excellent comprehensive performance.
[0049] like Figure 2As shown, the microstructure of this sample contains a large number of pores, which can be attributed to the oxidative expansion of graphene, which acts as a pore-forming agent, increases the porosity of the ceramic core, and is beneficial to the subsequent removal process.
[0050] Comparative Example 1
[0051] The 3D printed silicon-based ceramics in this comparative example are prepared using the same method and raw materials as in Example 1. The difference is that graphene is not added to the silicon-based composite ceramic powder in this comparative example.
[0052] Exposure performance tests were conducted on the comparative 3D printed silicon-based ceramics. The results showed that the over-curing width was 564.3 μm. Physical property tests were conducted on the obtained ceramic cores. The results showed that the shrinkage rate was 3.56% and the porosity was 23.12%.
[0053] Based on curing behavior analysis, graphene effectively reduces the over-curing width of the core through light absorption. During sintering, graphene can effectively reduce the sintering shrinkage of the core and increase porosity through oxidation, which is beneficial for dimensional accuracy and also helps with investment casting.
[0054] Example 2
[0055] The graphene-enhanced photopolymerizable 3D printed silicon-based ceramic of this embodiment is made from the following raw materials by volume fraction: 32% photosensitive resin, and the remainder is silicon-based composite ceramic powder.
[0056] The silicon-based composite ceramic powder is composed of the following raw materials in parts by weight: 70 parts matrix material, 25 parts mineralization modifier, and 0.0004 parts graphene.
[0057] The photosensitive resin is composed of the following raw materials in the indicated mass fractions: 5% photoinitiator, 10% dispersant, and the remainder being crosslinking aids;
[0058] The matrix material is fused silica; the fused silica includes fused silica with three particle size ranges in a mass ratio of 7:2:1: 0μm<d1≤5μm, 5μm<d2≤1μm, and 15μm<d2≤30μm.
[0059] The mineralization modifier is a powder mixture of silicon boride and zirconium boride with a particle size of 50 μm and a mass ratio of 1:1.
[0060] The crosslinking aid is composed of the following raw materials in parts by weight: 50 parts of 1,6-hexanediol diacrylate, 30 parts of trimethylolpropane triacrylate, 20 parts of isoborneol acrylate, and 20 parts of isoborneol methacrylate.
[0061] The dispersant is BYK9076 (BYK Chemical Dispersant-9076);
[0062] The photoinitiator is 1-hydroxycyclohexylphenyl ketone.
[0063] This embodiment also provides a method for preparing the above-mentioned graphene-enhanced photopolymerization 3D printed silicon-based ceramics, the method being as follows:
[0064] S1. Photosensitive resin and silicon-based composite ceramic powder are ball-milled at a speed of 300 rpm for 5 hours using zirconia ball milling beads as the medium to obtain a ceramic slurry that can be used for photocuring.
[0065] S2. Place the photopolymerizable ceramic slurry obtained in S1 into a ceramic 3D printer. Set the printing layer thickness to 150 μm, the ultraviolet wavelength to 405 nm, the exposure time to 5 s, and the exposure power to 30 mW / cm². 2 After layer-by-layer printing, a ceramic core blank is obtained;
[0066] S3. The ceramic core blank obtained in S2 is placed in a muffle furnace for degreasing treatment. Under air atmosphere, the temperature is increased from room temperature at a heating rate of 0.1℃ / min, and held at 200℃, 431℃, 508℃ and 600℃ for 1h respectively to obtain degreased silicon-based ceramic.
[0067] S4. Place the degreased silicon-based ceramic obtained in S3 into a sintering furnace, and heat it from room temperature to 1150℃ at a heating rate of 0.1℃ / min under an air atmosphere, hold it at that temperature for 8 hours, and then cool it down to 900℃ at a cooling rate of 1℃ / min. Finally, cool it down to room temperature with the furnace to obtain graphene-reinforced photopolymerized 3D printed silicon-based ceramic.
[0068] The graphene-reinforced photopolymer 3D printed silicon-based ceramic prepared in this embodiment has an over-curing width of 13.58 μm, a sintering shrinkage rate of 3.04%, and a porosity of 26.80%.
[0069] This embodiment also provides the application of the above-mentioned graphene-enhanced photopolymerization 3D printed silicon-based ceramics, which are used for precision casting of ceramic cores.
[0070] Example 3
[0071] The graphene-enhanced photopolymerizable 3D printed silicon-based ceramic of this embodiment is made from the following raw materials by volume fraction: 44% photosensitive resin, and the remainder is silicon-based composite ceramic powder.
[0072] The silicon-based composite ceramic powder is composed of the following raw materials in parts by weight: 80 parts matrix material, 20 parts mineralization modifier, and 0.0002 parts graphene.
[0073] The photosensitive resin is composed of the following raw materials by mass fraction: 1% photoinitiator, 5% dispersant, and the remainder is crosslinking aid;
[0074] The matrix material is fused silica; the fused silica includes fused silica with three particle size ranges in a mass ratio of 7:2:1: 0μm<d1≤5μm, 5μm<d2≤1μm, and 15μm<d2≤30μm.
[0075] The mineralization modifier is a powder mixture of silicon boride and zirconium boride with a particle size of 20 μm and a mass ratio of 1:1.
[0076] The crosslinking aid is composed of the following raw materials in parts by weight: 70 parts of 1,6-hexanediol diacrylate, 50 parts of trimethylolpropane triacrylate, 15 parts of isoborneol acrylate and 15 parts of isoborneol methacrylate.
[0077] The dispersant is product-110 (KOS110) from Guangzhou Kangou Shuang Trading Co., Ltd.
[0078] The photoinitiator is trimethylbenzoyl-diphenylphosphine oxide.
[0079] This embodiment also provides a method for preparing the above-mentioned graphene-enhanced photopolymerization 3D printed silicon-based ceramics, the method being as follows:
[0080] S1. Photosensitive resin and silicon-based composite ceramic powder are ball-milled at a speed of 500 rpm for 4 hours using zirconia ball milling beads as the medium to obtain a ceramic slurry that can be used for photocuring.
[0081] S2. Place the ceramic slurry obtained in S1 that can be photocured into a ceramic 3D printer. Set the printing layer thickness to 50μm, the ultraviolet wavelength to 405nm, the exposure time to 3s, and the exposure power to 10mW / cm. After printing layer by layer, a ceramic core blank is obtained.
[0082] S3. The ceramic core blank obtained in S2 is placed in a muffle furnace for degreasing treatment. Under air atmosphere, the temperature is increased from room temperature at a heating rate of 0.5℃ / min. After holding at 200℃, 431℃, 508℃ and 600℃ for 2 hours respectively, the degreased silicon-based ceramic is obtained.
[0083] S4. Place the degreased silicon-based ceramic obtained in S3 into a sintering furnace, and heat it from room temperature to 1250℃ at a heating rate of 0.5℃ / min under an air atmosphere, hold it at that temperature for 4 hours, and then cool it down to 900℃ at a cooling rate of 4℃ / min. Finally, cool it down to room temperature with the furnace to obtain graphene-reinforced photopolymerized 3D printed silicon-based ceramic.
[0084] The graphene-reinforced photopolymer 3D printed silicon-based ceramic prepared in this embodiment has an over-curing width of 2.79 μm, a sintering shrinkage rate of 2.77%, and a porosity of 26.69%.
[0085] The graphene-enhanced photopolymerization 3D printed silicon-based ceramic prepared in this embodiment is used for precision casting of ceramic cores.
[0086] Example 4
[0087] The graphene-enhanced photopolymerizable 3D printed silicon-based ceramic of this embodiment is made from the following raw materials by volume fraction: 40% photosensitive resin, and the remainder is silicon-based composite ceramic powder.
[0088] The silicon-based composite ceramic powder is composed of the following raw materials in parts by weight: 75 parts matrix material, 20 parts mineralization modifier, and 0.0001 parts graphene.
[0089] The photosensitive resin is composed of the following raw materials in the indicated mass fractions: 4% photoinitiator, 8% dispersant, and the remainder being crosslinking aids;
[0090] The matrix material is fused silica; the fused silica includes fused silica with three particle size ranges in a mass ratio of 5:4:1: 0μm<d1≤5μm, 5μm<d2≤1μm, and 15μm<d2≤30μm.
[0091] The mineralization modifier is a powder mixture of silicon boride and zirconium boride with a particle size of 20 μm and a mass ratio of 1:2.
[0092] The crosslinking aid is composed of the following raw materials in parts by weight: 50 parts of 1,6-hexanediol diacrylate, 30 parts of trimethylolpropane triacrylate, 10 parts of isoborneol acrylate and 10 parts of isoborneol methacrylate.
[0093] The dispersant is BYK111;
[0094] The photoinitiator is 1-hydroxycyclohexylphenyl ketone.
[0095] This embodiment also provides a method for preparing the above-mentioned graphene-enhanced photopolymerization 3D printed silicon-based ceramics, the method being as follows:
[0096] S1. Photosensitive resin and silicon-based composite ceramic powder are ball-milled at a speed of 600 rpm for 5 hours using zirconia ball milling beads as the medium to obtain a ceramic slurry that can be used for photocuring.
[0097] S2. Place the photopolymerizable ceramic slurry obtained in S1 into a ceramic 3D printer. Set the printing layer thickness to 100μm, the ultraviolet wavelength to 405nm, the exposure time to 4s, and the exposure power to 30mW / cm². 2 After layer-by-layer printing, a ceramic core blank is obtained;
[0098] S3. The ceramic core blank obtained in S2 is placed in a muffle furnace for degreasing treatment. Under air atmosphere, the temperature is increased from room temperature at a heating rate of 0.4℃ / min. After holding at 200℃, 431℃, 508℃ and 600℃ for 1h respectively, the degreased silicon-based ceramic is obtained.
[0099] S4. The degreased silicon-based ceramic obtained in S3 is placed in a sintering furnace and heated from room temperature to 1180℃ at a heating rate of 0.4℃ / min under an air atmosphere. The temperature is held for 5 hours and then cooled to 900℃ at a cooling rate of 3℃ / min. The temperature is then cooled to room temperature with the furnace to obtain graphene-reinforced photopolymerized 3D printed silicon-based ceramic.
[0100] The graphene-reinforced photopolymer 3D printed silicon-based ceramic prepared in this embodiment has an over-curing width of -25.28 μm, a sintering shrinkage rate of 2.72%, and a porosity of 27.39%.
[0101] The graphene-enhanced photopolymerization 3D printed silicon-based ceramic prepared in this embodiment is used for precision casting of ceramic cores.
[0102] Example 5
[0103] The graphene-enhanced photopolymerizable 3D printed silicon-based ceramic of this embodiment is made from the following raw materials by volume fraction: 42% photosensitive resin, and the remainder is silicon-based composite ceramic powder.
[0104] The silicon-based composite ceramic powder is composed of the following raw materials in parts by weight: 85 parts matrix material, 16 parts mineralization modifier, and 0.0001 parts graphene.
[0105] The photosensitive resin is composed of the following raw materials in the indicated mass fractions: 4% photoinitiator, 8% dispersant, and the remainder being crosslinking aids;
[0106] The matrix material is fused silica; the fused silica includes fused silica with three particle size ranges in a mass ratio of 6:3:1: 0μm<d1≤5μm, 5μm<d2≤1μm, and 15μm<d2≤30μm.
[0107] The mineralization modifier is a powder mixture of silicon boride and zirconium boride with a particle size of 20 μm and a mass ratio of 1:3.
[0108] The crosslinking aid is composed of the following raw materials in parts by weight: 600 parts of 1,6-hexanediol diacrylate, 300 parts of trimethylolpropane triacrylate, 12 parts of isoborneol acrylate, and 10 parts of isoborneol methacrylate.
[0109] The dispersant is BYK Chemical-111;
[0110] The photoinitiator is trimethylbenzoyl-diphenylphosphine oxide.
[0111] This embodiment also provides a method for preparing the above-mentioned graphene-enhanced photopolymerization 3D printed silicon-based ceramics, the method being as follows:
[0112] S1. Photosensitive resin and silicon-based composite ceramic powder are ball-milled at a speed of 600 rpm for 5 hours using zirconia ball milling beads as the medium to obtain a ceramic slurry that can be used for photocuring.
[0113] S2. Place the photopolymerizable ceramic slurry obtained in S1 into a ceramic 3D printer. Set the printing layer thickness to 60 μm, the ultraviolet wavelength to 405 nm, the exposure time to 4 s, and the exposure power to 112 mW / cm². 2 After layer-by-layer printing, a ceramic core blank is obtained;
[0114] S3. The ceramic core blank obtained in S2 is placed in a muffle furnace for degreasing treatment. Under air atmosphere, the temperature is increased from room temperature at a heating rate of 0.3℃ / min, and held at 200℃, 431℃, 508℃ and 600℃ for 1 h respectively to obtain degreased silicon-based ceramic.
[0115] S4. Place the degreased silicon-based ceramic obtained in S3 into a sintering furnace, and heat it from room temperature to 1200℃ at a heating rate of 0.3℃ / min under an air atmosphere, hold it at that temperature for 6 hours, and then cool it down to 900℃ at a cooling rate of 2℃ / min. Finally, cool it down to room temperature with the furnace to obtain graphene-reinforced photopolymerized 3D printed silicon-based ceramic.
[0116] The graphene-reinforced photopolymer 3D printed silicon-based ceramic prepared in this embodiment has an over-curing width of -50.34 μm, a sintering shrinkage rate of 2.70%, and a porosity of 26.80%.
[0117] The graphene-enhanced photopolymerization 3D printed silicon-based ceramic prepared in this embodiment is used for precision casting of ceramic cores.
[0118] like Figure 1As shown in the figure, (a) to (e) are optical microscope images of samples with graphene contents of 0.2‰, 0.4‰, 0.6‰, 0.8‰, and 1.0‰, respectively. The red arrows indicate the over-curing width of the samples. As the graphene content increases from 0.2‰ to 1‰, the over-curing width gradually decreases, from 52.09 μm to -50.34 μm. However, as the graphene content exceeds 0.6‰, the cured sample outline gradually becomes jagged, and internal pores appear. This indicates that photocuring is significantly suppressed.
[0119] like Figure 3 As shown, (a) Figure shows the effect of graphene on the macroscopic morphology of the test rod, (b) Figure shows the designed model and the complex structure model, indicating that graphene can realize the preparation of complex samples, (c) Figure shows the SEM image of the complex sample, indicating that the actual size matches the design size, and (d) Figure shows the energy spectrum, indicating that various elements are uniformly distributed inside the sample. Figure 3 Samples prepared with a graphene content of 0.6‰ were presented, and their macroscopic morphology was compared with that of samples without graphene. A noticeable warping phenomenon was observed in the samples, which is attributed to stress concentration caused by photocuring. The incorporation of graphene effectively alleviated this phenomenon, significantly improving the dimensional accuracy of the samples. The dimensions of the complex-structured samples were measured using SEM, and they matched the design model, indicating that the addition of graphene can achieve the fabrication of high-precision ceramic cores.
[0120] like Figure 4 As shown, Figure 4 (a) shows the effect of different amounts of graphene on porosity and packing density. With increasing graphene content, the apparent porosity of the ceramic core increased from 24.33% to 27.72%. Conversely, the packing density increased from 1.75 g / cm³. 3 It decreased to 1.65 g / cm³ 3 The main reason for this phenomenon is the oxidation reaction of graphene, which produces CO2, improving the porosity inside the core and leading to a decrease in packing density. The addition of graphene gradually increases the flexural strength of the ceramic core. Figure 4 (b) The pressure increased from 10.48 MPa to 13.97 MPa, then decreased slightly to 13.53 MPa. This can be explained by the fact that ceramic slurries containing 0.2‰ graphene have a larger S... dThis allows for achieving the same curing depth at relatively low exposure energies. Therefore, weak interlayer adhesion typically leads to interlayer cracking and decreased flexural strength. Notably, porosity and flexural strength increase simultaneously with increasing graphene content. This is attributed to the fact that when graphene content is low, the main factor affecting flexural strength is internal defects caused by weak interlayer bonding during curing. However, as graphene content gradually increases, the increase in apparent porosity affects core strength, resulting in a slight decrease in core strength. When the graphene content is 0.2‰, the high-temperature flexural strength of the core is limited to only 8.64 MPa. This is mainly due to thermal stress, leading to accelerated interlayer cracking. With increased interlayer adhesion, the high-temperature flexural strength reaches a stable level of around 16 MPa. Figure 4 (c) describes the effect of graphene content on the sintering shrinkage of the ceramic core. The sintering shrinkage rate decreases with increasing graphene content, which can be attributed to the volume expansion effect caused by graphene oxidation. The shrinkage rate along the Z-axis (i.e., the printing direction) is much higher than that along the X and Y axes. This is attributed to the technical characteristics of the VPP-3D layer-by-layer printing process, which leads to the formation of interlayer gaps, thus exacerbating shrinkage. High-temperature creep resistance of the ceramic core is essential and closely related to the dimensional accuracy of the turbine blades. Figure 4 (d) illustrates the effect of graphene content on the deformation of ceramic cores at high temperatures. With increasing graphene content, the high-temperature deflection of the ceramic core initially decreases and then increases. Due to the high solids load in the ceramic slurry, cores with low graphene content do not exhibit significant deflection at high temperatures, despite the presence of cracks between layers. With increasing graphene content, the deflection initially decreases to 1.46 mm and then gradually reaches 1.63 mm. The increase in deflection can be attributed to the increase in apparent porosity, leading to a decrease in the effective load-bearing area within the ceramic, thus resulting in increased creep.
[0121] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.
Claims
1. A graphene-reinforced photopolymerizable 3D printed silicon-based ceramic, characterized in that, The graphene-enhanced photopolymerizable 3D printed silicon-based ceramic is made from the following raw materials by volume fraction: 32% to 44% photosensitive resin, with the remainder being silicon-based composite ceramic powder; The silicon-based composite ceramic powder is composed of the following raw materials in parts by weight: 70 to 90 parts matrix material, 10 to 25 parts mineralization modifier, and 0 parts < graphene < 0.1 parts. The photosensitive resin is composed of the following raw materials in the indicated mass fractions: 1%–5% photoinitiator, 5%–10% dispersant, and the remainder being crosslinking aids; The matrix material is fused silica; The mineralization modifier is a mixture of silicon boride and zirconium boride; The crosslinking aid is a mixture of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, isoborneol acrylate, and isoborneol methacrylate; The dispersant is BYK9076, BYK111, or KOS110; The photoinitiator is 1-hydroxycyclohexylphenyl ketone or trimethylbenzoyl-diphenylphosphine oxide; The fused silica includes fused silica with three particle size ranges: 0μm < d1 ≤ 5μm, 5μm < d2 ≤ 15μm, and 15μm < d2 ≤ 30μm.
2. The graphene-reinforced photopolymerizable 3D printed silicon-based ceramic according to claim 1, characterized in that, The crosslinking aid is composed of the following raw materials in parts by weight: 50 to 70 parts of 1,6-hexanediol diacrylate, 20 to 50 parts of trimethylolpropane triacrylate, 10 to 20 parts of isoborneol acrylate, and 10 to 20 parts of isoborneol methacrylate.
3. The graphene-reinforced photopolymerizable 3D printed silicon-based ceramic according to claim 1, characterized in that, The mineralization modifier is a powder with a particle size of 20 μm to 50 μm.
4. A method for preparing graphene-reinforced photopolymerizable 3D printed silicon-based ceramics as described in any one of claims 1-3, characterized in that, The method is as follows: S1. The photosensitive resin and silicon-based composite ceramic powder are ball-milled at a speed of 300 rpm to 600 rpm for 3 to 5 hours to obtain a ceramic slurry that can be used for photocuring. S2. Place the photopolymerizable ceramic slurry obtained in S1 into a ceramic 3D printer. Set the printing layer thickness to 50μm–150μm, the ultraviolet wavelength to 405 nm, the exposure time to 3s–5s, and the exposure power to 10 mW / cm²–30 mW / cm². 2 After layer-by-layer printing, a ceramic core blank is obtained; S3. The ceramic core blank obtained in S2 is placed in a muffle furnace for degreasing treatment. Under air atmosphere, the temperature is increased from room temperature at a heating rate of 0.1℃ / min to 0.5℃ / min. After holding at 200℃, 431℃, 508℃ and 600℃ for 1 h to 2 h respectively, the degreased silicon-based ceramic is obtained. S4. Place the degreased silicon-based ceramic obtained in S3 into a sintering furnace. Under an air atmosphere, heat the ceramic from room temperature to 1150℃ to 1250℃ at a heating rate of 0.1℃ / min to 0.5℃ / min, hold it at that temperature for 4h to 8h, and then cool it to 900℃ at a cooling rate of 1℃ / min to 4℃ / min. Finally, cool the ceramic to room temperature with the furnace to obtain graphene-reinforced photopolymerized 3D printed silicon-based ceramic.
5. The method according to claim 4, characterized in that, The graphene-enhanced photopolymerization 3D printed silicon-based ceramic described in S4 has an over-curing width of -50.34μm to 52.09μm, a sintering shrinkage rate of 2.70% to 3.16%, and a porosity of 26.69% to 27.7%.
6. An application of a graphene-reinforced photopolymerizable 3D printed silicon-based ceramic prepared by the method described in claim 4, characterized in that, The graphene-enhanced photopolymerization 3D printed silicon-based ceramic is used for precision casting of ceramic cores.
Citation Information
Patent Citations
Zero-sintering-shrinkage aluminum-based ceramic core material for photocuring additive manufacturing
CN117303870A
Silicon-based ceramic core based on photocuring 3D printing and preparation method thereof
CN118724572A
Photocuring 3D printing silicon-based ceramic core slurry as well as preparation method and application thereof
CN118754707A